2014
DOI: 10.5578/mb.7782
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Acid Proteinase and Phospholipase Activity as Virulence Factors in Clinical Aspergillus spp. Isolates

Abstract: ÖZETAspergillus türleri doğada yaygın olarak bulunmakta ve özellikle immün sistemi baskılanmış hastalarda ciddi enfeksiyonlara yol açabilmektedir. Aspergillus fumigatus kompleks insanlarda aspergilloz enfeksiyonlarından en sık izole edilen etken olmakla beraber; Aspergillus flavus kompleks ve Aspergillus niger kompleks de son zamanlarda önemi artan enfeksiyon etkenleri olmuşlardır. İnvazif aspergilloz enfeksiyonlarının gelişiminde rol oynayan faktörler arasında; immün süpresyon, hematolojik malignensi ve korti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
1
2
0
3
Order By: Relevance
“…Results showed that (62.5%) A. fumigatus, (50%) of A. terreus and (100%) of A. niger, F. solani and A. alternata of each for them isolates were positive for phospholipase production, as shown in Table (5). Our results were relatively agreed with the results of Birinci et al (2014) was detected of phospholipase activity in 30(93.3%) of A. fumigatus, 4(25%) and None of nine A. flavus isolates exhibited phospholipase activity.…”
Section: Csupporting
confidence: 91%
“…Results showed that (62.5%) A. fumigatus, (50%) of A. terreus and (100%) of A. niger, F. solani and A. alternata of each for them isolates were positive for phospholipase production, as shown in Table (5). Our results were relatively agreed with the results of Birinci et al (2014) was detected of phospholipase activity in 30(93.3%) of A. fumigatus, 4(25%) and None of nine A. flavus isolates exhibited phospholipase activity.…”
Section: Csupporting
confidence: 91%
“…Highest lipase activity, protease activity, α-amylase activity and pectinase activity was also prominent for corneal isolate of Aspergillus species [3]. A study also carried by Birinci A et al, showed 30 A. fumigatus, nine A. flavus and four A. niger strains isolated from clinical specimens [3,28]. Where A. fumigatus showed proteinase 76.7% (23/30) and phospholipase activity 93.3% (28/30).…”
Section: Discussionmentioning
confidence: 99%
“…BSA agar plakları, %2 glukoz (Sigma), %0.01 KH 2 PO 4 (Sigma), %0.05 MgSO 4 (Sigma), %2 agar ve %1 BSA (Sigma) eklenerek hazırlanmış-tır. Plaklar 37°C'de 3. gün bekletilmiş, koloninin çevresinde halo oluşmasıyla değerlendiril-miştir (17)(18)(19) .…”
Section: İn Vitro Virülans çAlışmalarıunclassified